Metode Diskusi Terhadap Perkembangan Kognitif Siswa Pada Mata Pelajaran Qur'an-Hadits MTs Hidayatul Muttallimin - Muhamad Ripin Ikwandi (Darajat: Jurnal Pendidikan Agama Islam, 2020)
Education is a conscious endeavor and aims to develop human qualities. As a goal-conscious activity, its implementation is in a continuous process in every type and level of education, all related to an integral educational system. Education as a system is nothing but a functional totality that exists in an organized system and cannot be separated from a series of elements or components that are dynamically related in a unit. From the above background a problem arises, so that the authors formulate the problem as follows, 1) How is the implementation of the discussion method in the Qur'an-Hadith subject at MTs Hidayatul Muttaallimin Wonoayu Sidoarjo ?; 2) How is the cognitive development of students in the Qur'an-Hadits subject at MTs Hidayatul Muttaallimin Wonoayu Sidoarjo ?; 3) How is the effect of the discussion method on students' cognitive development in the Qur'an-Hadith subject at MTs Hidayatul Muttaallimin Wonoayu Sidoarjo? The cognitive development of students in the subject of Qur'an Hadith at MTs Hidayatul Muttaallimin Wonoayu Sidoarjo is quite good. This is evidenced by the results of research which show that the percentage of students 'cognitive development in the Qur'an-Hadith subject is 80%, which is quite good. That there is an effect of the discussion method on students' cognitive development in the Qur'an-Hadith subject. MTs Hidayatul Muttaallimin Wonoayu Sidoarjo. See changes in the initial value before using the discussion method and by using the discussion method